Successive Surface Reactions on Hydrophilic Silica for Modified Magnetic Nanoparticle Attachment Probed by Sum-Frequency Generation Spectroscopy - Jeeranan Nonkumwong (2018)
© 2018 American Chemical Society. Successive surface reactions on hydrophilic silica substrates were designed and performed to immobilize ethanolamine-modified magnetic ferrite-based nanoparticle (NP) for surface characterization. The various surfaces were monitored using sum-frequency generation (SFG) spectroscopy. The surface of the hydrophilic quartz substrate was first converted to a vinyl-terminated surface by utilizing a silanization reaction, and then, the surface functional groups were converted to carboxylic-terminated groups via a thiol-ene reaction. The appearance and disappearance of the vinyl (=CH2) peak at ∼2990 cm-1 in the SFG spectra were examined to confirm the success of the silanization and thiol-ene reactions, respectively. Acyl chloride (-COCl) formation from carboxy (-COOH) functional group was then performed for further attachment of magnetic amine-functionalized magnesium ferrite nanoparticles (NPs) via amide bond formation. The scattered NPs attached on the modified silica substrate was then used to study the changes in the spectral profile of the ethanolamine modifier of the NPs for in situ lead(II) (Pb2+) adsorption at the solid-liquid interface using SFG spectroscopy. However, due to the limited number of NPs attached and sensitivity of SFG spectroscopy toward expected change in the modifier spectroscopically, no significant change was observed in the SFG spectrum of the modified silica with magnetic NPs during exposure to Pb2+ solution. Nevertheless, SFG spectroscopy as a surface technique successfully monitored the modifications from a clean fused substrate to -COCl formation that was used to immobilize the decorated magnetic nanoparticles. The method developed in this study can provide a reference for many surface or interfacial studies important for selective attachment of adsorbed organic or inorganic materials or particles.